Now and then [videorecording (DVD)] - Glatter, Lesli Linka; Ricci, Christina; Birch, Thora; Hoffmann, Gaby, 1982-; Griffith, Melanie, 1957-; Moore, Demi; O'Donnell, Rosie; Wilson, Rita (New Line Home Video, 1999)
A heartwarming comedy about the childhood mischief of four best friends who reunite after twenty years.